RESPON STEK MERANTI BAKAU (Shorea uliginosa Foxw.) TERHADAP PEMBERIAN ROOTONE F DAN BERBAGAI MEDIA TANAM - Azwin, Azwin; Sadjati, Emy (Fakultas Kehutanan Universitas Lancang Kuning, 2018)
From the exploration results at Biosphere Reserve GSK-BB Riau in 2009 together with Tokyo University of Agriculture, found that Meranti Bakau (Shorea uliginosa Foxw.) has the potential to produce high bioethanol. So one needs to be developed is done vegetatively propagation through shoot cuttings. This study aims to obtain a dose of Rootone F and Media Planting appropriate for the growth and development of shoot cuttings. The method used is complete factorial randomized design that is first factor of dose of rootone F 1 g/l water, rootone F 2 g/l water and rootone F 3 g/l water. The second factor is the type of soil media: peat soil + sand 1: 1, peat + sand 2: 1 and peat + sand 3: 1. The results showed that the use of Rootone F and peat soil media and sand at various treatment doses can not give growth to the shoot cuttings of meranti bakau plants. The combination of Rootone F dosage and peat soil media and sand can not provide good growth in shoot cuttings.